Gambaran Kesadaran Perokok Untuk Mengikuti Konseling Di Klinik Berhenti Merokok Di Kota Denpasar - Ni Luh Putu Devhy; Ns. A. A. Istri Dalem Hana Yundari; Ika Setya Purwanti; Diah Prihartiningsih (Jurnal Kesehatan Indonesia, 2019)
Abstract Introduction The Smoking Cessation Clinic (SCC) is one of the government's efforts to reduce the number of smokers. The SCC is expected to help people who want to quit smoking. This study aims to describe the awareness of smokers to quit smoking through the clinical consultation service to stop smoking in the city of Denpasar. Method: The design of this study was a cross-sectional study conducted at Puskesmas in the city of Denpasar for 3 months from July to November 2018. Samples were selected using consecutive sampling of 33 people. Data was collected using a structure questionnaire. Results: The results found the potensial utilization of SCC in Denpasar City Health Center was very high, as 25 respondents (75.8%) suggested that their families use the SCC. The opinion of the puskesmas visitors to teaching and learning activities was that most or 57.6% stated that the smoking cessation clinic was effective in making smokers quit smoking. In 2017 there were 177 people use SCC and those who managed until quite smoking are only 5 people. Discussion: The level of utilization of teaching and learning activities is still low because there are still many visitors in the Public Health Centers who are not aware of it. Most of diseases and health problems are related to smoking therefor collaboration SCC with others program are important. All health officers at others program should ask and recommend patient and the family to SCC if there any smokers.